Improved GA and Its Application in Performance Optimization of Electronic Components - Wenrui Zhao; Borui Wu (Advances in Multimedia)
In order to improve the performance optimization effect of electronic components, this paper uses the improved GA to construct the performance optimization system of electronic components. Moreover, this paper proposes an optimized reliability allocation process method based on cost function, which further optimizes the reliability design of electronic circuit systems. In addition, this paper conducts a sensitivity analysis of the electronic circuit system and compares and analyzes the evaluation results of component sensitivity and comprehensive importance based on simulation. Finally, this paper compares and demonstrates the different influences of various components in the electronic circuit system on the whole system. The experimental research shows that the performance optimization system of electronic components based on the improved GA proposed in this paper has a certain effect on improving the performance of electronic components.